Pengaruh Influencer Marketing dan Live Shopping Pada Tiktokshop Terhadap Keputusan Pembelian Produk â€œEat Sambelâ€ - Susilo, Kristianto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze the influence of influencer marketing and TikTok Shop on increasing sales of